Representasi Aspirasi Daerah dalam Koordinasi DPD RI dan Pemerintah Daerah Provinsi Bengkulu - Farida Nur Aini; Susiyanto Susiyanto; Eni Khairani; Novella Firsty Putri Diantra (Aceh Anthropological Journal, 2026)
This article analyzes the effectiveness of coordination between members of the Regional Representative Council of the Republic of Indonesia (DPD RI) from Bengkulu Province and the Bengkulu Provincial Government in advocating community aspirations for regional development. The study is based on the unclear working mechanism between DPD RI as a regional representative institution at the national level and the provincial government as the administrator of regional autonomy. From a socio-anthropological perspective, regional aspirations are understood not merely as administrative proposals, but also as expressions of local interests, experiences of development inequality, and demands for recognition within central–local relations. This study uses a descriptive qualitative approach through in-depth interviews, observation, and document analysis. The informants include a DPD RI member from Bengkulu Province, the Head of the DPD RI Representative Office in Bengkulu, the Regional Secretary of Bengkulu Province, and community figures. The analysis focuses on three coordination mechanisms: mutual adjustment, direct supervision, and the standardization of procedures, outputs, and skills. The findings show that coordination has taken place through formal and informal communication, particularly in the aspiration-gathering stage. However, coordination remains ineffective in the stage of advocating these aspirations to the central government because there is no standard operating procedure governing joint work mechanisms. This article emphasizes the need to institutionalize coordination so that regional aspirations do not stop at the collection stage but are systematically advocated through national policy processes. Abstrak: Artikel ini menganalisis efektivitas koordinasi antara Anggota Dewan Perwakilan Daerah Republik Indonesia (DPD RI) Provinsi Bengkulu dan Pemerintah Daerah Provinsi Bengkulu dalam memperjuangkan aspirasi masyarakat untuk peningkatan pembangunan daerah. Kajian ini berangkat dari belum jelasnya mekanisme hubungan kerja antara DPD RI sebagai representasi daerah di tingkat nasional dan pemerintah daerah sebagai penyelenggara otonomi daerah. Dalam perspektif sosial-antropologis, aspirasi daerah tidak hanya dipahami sebagai daftar usulan administratif, tetapi juga sebagai ekspresi kepentingan lokal, pengalaman ketimpangan pembangunan, dan kebutuhan pengakuan dalam relasi pusat–daerah. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui wawancara mendalam, observasi, dan telaah dokumen. Informan penelitian meliputi Anggota DPD RI Provinsi Bengkulu, Kepala Kantor Perwakilan DPD RI Provinsi Bengkulu, Sekretaris Daerah Provinsi Bengkulu, dan tokoh masyarakat. Analisis difokuskan pada tiga mekanisme koordinasi, yaitu saling mengingatkan, supervisi langsung, dan standardisasi prosedur, hasil, serta keterampilan. Hasil penelitian menunjukkan bahwa koordinasi telah berlangsung melalui komunikasi formal dan informal, terutama dalam penjaringan aspirasi. Namun, koordinasi belum efektif pada tahap pengawalan aspirasi ke pemerintah pusat karena belum tersedia SOP yang mengatur pola kerja bersama. Artikel ini menegaskan pentingnya pelembagaan koordinasi agar aspirasi daerah tidak berhenti pada penjaringan, tetapi terkawal hingga proses kebijakan nasional.